ETIKA BERBAHASA DALAM PELAYANAN PUBLIK - Suhartono Suhartono; Enny Dwi Lestariningsih (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2016)
Services in the bureaucracy are still complained by the public. It means that the service within the bureaucracy still needs to be improved. Society calls for excellent service. Excellent service is a service to meet the expectations and needs of the community/customer. Bureaucracy in serving the public needs to consider the principles of the excellent service, which is the principle (1) ability, (2) attitude, (3) appearance, (4) attention, (5) action, and (6) accounttability, (7)"Human Relations", (8) reliability, (9) responsiveness, and (10) assurance. These principles are communicated with language. Without language, it is difficult to communicate. The use of language in excellent service must be ethical. Speaking ethics in excellent service are implemented in all forms of service, is when greeting customers. When talking on the phone, and when inscribed. Speaking ethics are constructed by watching the attitude and choice of words. Choice of words is determined by the elements of the communication, namely the speaker and listener, talking material, place, time, and communication media. Without ethics in speaking, the public impression of the apparatus on an institution would be bad or unpleasant.